Evidencia de una reimanación terciaria en las Béticas Occidentales. Implicaciones tectónicas. - García - Dueñas, V.; Osete, María Luisa; Vegas, R.; Villalaín, J.J. (Física de la Tierra, 1992)
Sin resumen